Titanium oxide modified graphite phase carbon nitride nano-composite plugging agent and oil-based drilling fluid

By developing titanium oxide-modified graphite phase carbon nitride nanocomposite sealant, the problem that the existing technology cannot effectively seal nanopore joints in mud shale formations is solved, and the stability of the well wall and the performance of the drilling fluid are improved.

CN119912912APending Publication Date: 2025-05-02SOUTHWEST PETROLEUM UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510085713.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-20
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

The prior art cannot effectively seal the nanopore gaps in mud shale formations, resulting in the problem of instability of the well wall.

Method used

A titanium oxide-modified graphite phase carbon nitride nanocomposite sealant has been developed, with a particle size of nanometers. It is prepared through specific synthesis steps to effectively seal nanopores in mud shale formations.

Benefits of technology

This sealing agent can effectively reduce the entry of drilling fluid filtrate into the formation, prevent the hydration and expansion of mud shale, stabilize the well wall, and improve the rheology, stability and sealing of drilling fluid.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005250087200000091
    Figure BDA0005250087200000091
  • Figure HDA0005250087210000011
    Figure HDA0005250087210000011
  • Figure HDA0005250087210000012
    Figure HDA0005250087210000012
Patent Text Reader

Abstract

The invention discloses a titanium oxide modified graphite phase carbon nitride nano-composite plugging agent and an oil-based drilling fluid. The titanium oxide modified graphite phase carbon nitride nanosheet composite blocking agent is prepared from the following synthetic raw materials: melamine, tetrabutyl titanate, phosphorous acid, glycerol, ethanol, ethylene glycol, an initiator and deionized water. The drilling fluid comprises the titanium oxide modified graphite phase carbon nitride nano composite plugging agent provided by the invention. The particle size distribution of the titanium oxide modified graphite phase carbon nitride nano-composite blocking agent is 350-620 nm, nano-sized pores in a shale well wall can be effectively blocked, so that the well wall can be effectively stabilized, collapse can be prevented, and meanwhile, the preparation method is reliable in principle and has a wide market prospect; the oil-based drilling fluid used in the invention has good rheological property, stability, plugging property and other properties under shale formation conditions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of oil industry drilling, and specifically designs the synthesis of a titanium oxide-modified graphite phase carbon nitride nanocomposite plugging agent and an oil-based drilling fluid containing the plugging agent. Background Art

[0002] Oil-based drilling fluid is an emulsion with oil as continuous phase and water as dispersed phase. It is made of diesel, mineral oil or synthetic oil as base oil, supplemented with emulsifiers, weighting agents, filtration agents and other functional additives. Compared with water-based drilling fluid, its advantages are stronger inhibition, lubricity and high temperature resistance. At present, it has achieved excellent results in various complex formations and has broad application prospects.

[0003] In recent years, with the rapid development of China's economy, China's natural gas dependence on foreign countries has reached 42.4%, and natural gas production is difficult to meet the needs of social industrial development. Therefore, the exploration and development of unconventional resources such as shale gas has become the focus of ensuring national energy security. The shale gas in the Sichuan Basin is the main force of shale gas exploration and development in my country. The mud shale layer of the Longmaxi Formation has strong rationality and developed microcracks, which leads to strong self-absorption after contact with fluid, causing the cracks to initiate, expand, and penetrate to form macro cracks, which are prone to complex wellbore instability during drilling. The development of excellent plugging agents to reduce drilling fluid loss and improve wellbore stability has always been the difficulty and focus of oil-based drilling fluid research. For the micron-level cracks in shale formations, the application of existing micron-level plugging agents has a good effect, but in terms of plugging nano-level cracks, its plugging effect needs to be further improved. Therefore, the key to developing size-matched nano-level plugging agents and adding them to oil-based drilling fluids is to improve the plugging performance of shale nano-level cracks and reduce the occurrence of complex situations such as wellbore instability. Summary of the invention

[0004] In view of the problem of wellbore instability caused by the inability of current conventional plugging agents to effectively plug nanopores in shale, the present invention provides a titanium oxide-modified graphite phase carbon nitride nanocomposite plugging agent with a nanometer particle size, which can effectively plug the nanopores in shale formations, thereby achieving the purpose of stabilizing the wellbore wall.

[0005] To achieve the above object, the technical scheme of the present invention is as follows: the raw materials of the titanium oxide modified graphite phase carbon nitride nanocomposite plugging agent are melamine, tetrabutyl titanate, phosphorous acid, glycerol, ethanol, ethylene glycol, initiator, and deionized water. The preparation steps of the titanium oxide modified graphite phase carbon nitride nanocomposite plugging agent are as follows:

[0006] Step 1, add tetrabutyl titanate to a dispersion of deionized water, ultrasonically disperse it, then drop an initiator at a rate of 2 mL / min while stirring, then react at 50-60° C., cool to room temperature, separate by centrifugation, ultrasonically disperse it again, filter it, adjust the sol concentration, and obtain a pure titanium oxide sol.

[0007] Step 2: adding melamine and phosphorous acid to deionized water to dissolve, then stirring for a period of time in a water bath, placing in a sealed high-pressure reactor to react after stirring, filtering, washing, and drying to obtain a precursor after the reaction, adding the precursor to a mixed solution of glycerol and ethanol, then refluxing in an oil bath, cooling, washing with anhydrous ethanol, and drying to obtain an intermediate product, and calcining to obtain graphite phase carbon nitride nanosheets.

[0008] Step 3, mixing ethanol and ethylene glycol to obtain a mixed solution; adding titanium oxide sol, stirring and ultrasonically dispersing to obtain a titanium oxide sol dispersion, adding graphite phase carbon nitride nanosheets, stirring and ultrasonically dispersing to obtain a graphite phase carbon nitride nanosheet dispersion, then mixing the two dispersions, ultrasonically dispersing, reacting at 50-60°C, cooling to room temperature, filtering, washing, drying, and calcining at high temperature to obtain a titanium oxide-modified graphite phase carbon nitride nanocomposite plugging material.

[0009] In step 1, the volume ratio of tetrabutyl titanate to deionized water is 10 mL:40 mL;

[0010] The initiator in step 1 is hydrogen chloride (HCl), sulfuric acid (H 2 SO 4 ), sodium hydroxide (NaOH), potassium hydroxide (KOH), and the concentration of titanium oxide sol is adjusted to 20 mg / mL;

[0011] In the step 2, the temperature of the water bath is 60-90° C., and the stirring period is 0.5-2 hours; the temperature of the reaction in the high-pressure reactor is 120-200° C., and the time is 6-24 hours.

[0012] In the step 2, the dosage ratio of melamine, phosphorous acid and deionized water is 1:1-5 g:100 mL, and the dosage ratio of the precursor to the mixed solution is 0.6 g:10-50 mL;

[0013] In the step 2, the volume ratio of the glycerol and ethanol mixed solution is 10 mL: 10-60 mL; the temperature of the oil bath is 60-120° C., and the reflux time is 2-6 hours; the temperature of the calcination is 350-600° C., and the time is 1-5 hours;

[0014] In the step 3, the volume ratio of the ethanol and ethylene glycol solution is 1:1; the volume ratio of the titanium oxide sol to the ethanol and ethylene glycol mixed solution is 10-40 mL:40 mL; the amount ratio of the graphite phase carbon nitride nanosheets to the ethanol and ethylene glycol mixed solution is 10-40 mg:40 mL;

[0015] The drying temperature in steps 2 and 3 is 60-150° C. and the drying time is 5-10 hours; the high-temperature calcination in step 3 is 500-600° C. and the calcination time is 2-4 hours.

[0016] Another object of the present invention is to provide an oil-based drilling fluid, to which the titanium oxide-modified graphite-phase carbon nitride nanocomposite plugging agent of the present invention is added.

[0017] The composition of the drilling fluid is as follows, in parts by weight: 225-227 parts of 5# white oil, 7-8 parts of organic soil MOGEL, 3.6-3.8 parts of primary emulsifier HIEMUL, 9.8-10.2 parts of auxiliary emulsifier HICOAT, 3.2-3.3 parts of wetting agent MOWET, 14.5-15.5 parts of filtrate reducer HIFLO, 0.7-0.8 parts of shear enhancer ML-CSON, 24-26 parts of 25-35% calcium chloride solution, 7.3-7.7 parts of calcium oxide, 1.25-3.75 parts of titanium oxide modified graphite phase carbon nitride nanocomposite plugging agent, 250-600 parts of barite powder, and a density of 1.5-2.1 g / cm 3 .

[0018] The beneficial effects of the present invention are as follows:

[0019] The particle size distribution of the titanium oxide modified graphite phase carbon nitride nanocomposite plugging agent prepared by the present invention is between 350 and 620 nm, and it can effectively plug the nano-level pores in the mudstone formation, reduce the entry of drilling fluid filtrate into the formation, and prevent the mudstone from hydrating and expanding to cause the mechanical properties to deteriorate, thereby achieving the effect of stabilizing the well wall; the oil-based drilling fluid used by the present invention has good performance in rheology, stability and plugging properties under mudstone formation conditions. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 This is a particle size distribution diagram of the titanium oxide modified graphite phase carbon nitride nanocomposite plugging agent in Example 1;

[0021] Figure 2 This is a particle size distribution diagram of the titanium oxide modified graphite phase carbon nitride nanocomposite plugging agent in Example 2; DETAILED DESCRIPTION

[0022] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0023] 1. Synthesis of Titanium Oxide Modified Graphite Phase Carbon Nitride Nanocomposite Plugging Agent:

[0024] Embodiment 1:

[0025] Preparation of titanium oxide sol and graphite phase carbon nitride nanosheets: 10 mL of tetrabutyl titanate was added to 40 mL of deionized water dispersion for ultrasonic dispersion for 30 min, and then a 5 mol / L sodium hydroxide solution was added dropwise at a rate of 2 mL / min while stirring, and then reacted at 50-60 ° C, cooled to room temperature, centrifuged and separated, and then ultrasonically dispersed, filtered, and the concentration of titanium oxide sol was adjusted to 20 mg / mL to obtain titanium oxide sol. Then, 1.0 g of melamine and 3.0 100 mL of phosphorous acid was added into 100 mL of deionized water to dissolve, and then stirred in a water bath at 80 ° C for 1 h, and then placed in a sealed high-pressure reactor for reaction at 150 ° C for 6 h. After the reaction, the precursor was obtained by suction filtration, washing and drying. 0.6 g of the precursor was added into a mixed solution of 5 mL of glycerol and 25 mL of ethanol, and then refluxed in an oil bath at 90 ° C., cooled to room temperature, washed with anhydrous ethanol, and dried at 65 ° C to obtain an intermediate product, which was calcined at 400 ° C for 3 h to obtain graphite phase carbon nitride nanosheets.

[0026] Synthesis of titanium oxide modified graphite phase carbon nitride nanocomposite plugging material: 15 mL of titanium oxide sol and 15 mg of graphite phase carbon nitride nanosheets were respectively added to 40 mL of a mixed solution of ethanol and ethylene glycol, and ultrasonically dispersed for 45 minutes to obtain a titanium oxide sol dispersion and a graphite phase carbon nitride nanosheet dispersion. The two dispersions were then mixed and ultrasonically dispersed for 45 minutes. After reacting at 50-60°C for 4 hours, the mixture was cooled to room temperature, filtered, washed, dried, and calcined at 500°C for 3 hours to obtain a titanium oxide modified graphite phase carbon nitride nanocomposite plugging material.

[0027] Embodiment 2:

[0028] Preparation of titanium oxide sol and graphite phase carbon nitride nanosheets: 10 mL of tetrabutyl titanate was added to 40 mL of deionized water dispersion for ultrasonic dispersion for 45 min, and then a 5 mol / L hydrogen chloride solution was added dropwise at a rate of 2 mL / min while stirring, and then reacted at 50-60 ° C, cooled to room temperature, centrifuged and separated, and then ultrasonically dispersed, filtered, and the concentration of titanium oxide sol was adjusted to 20 mg / mL to obtain titanium oxide sol. Then, 1.0 g of melamine and 4.0 g of Phosphorous acid was added to 100 mL of deionized water to dissolve, then stirred in a water bath at 80°C for 1 h, then placed in a sealed high-pressure reactor at 150°C for reaction for 7 h, filtered, washed, and dried to obtain a precursor, 0.6 g of the precursor was added to a mixed solution of 10 mL of glycerol and 30 mL of ethanol, then refluxed in an oil bath at 90°C, cooled to room temperature, washed with anhydrous ethanol, and dried at 65°C to obtain an intermediate product, which was calcined at 450°C for 3 h to obtain graphite phase carbon nitride nanosheets.

[0029] Synthesis of titanium oxide modified graphite phase carbon nitride nanocomposite plugging material: 20 mL of titanium oxide sol and 20 mg of graphite phase carbon nitride nanosheets were respectively added to 40 mL of a mixed solution of ethanol and ethylene glycol, and ultrasonically dispersed for 60 minutes to obtain a titanium oxide sol dispersion and a graphite phase carbon nitride nanosheet dispersion. The two dispersions were then mixed and ultrasonically dispersed for 60 minutes. After reacting at 50-60°C for 4 hours, the mixture was cooled to room temperature, filtered, washed, dried, and calcined at 500°C for 3.5 hours to obtain a titanium oxide modified graphite phase carbon nitride nanocomposite plugging material.

[0030] 2. Preparation of oil-based drilling fluid:

[0031] The present invention mainly describes the application of titanium oxide modified graphite phase carbon nitride nanocomposite plugging agent with the following specific formula. Based on 225 parts by weight of base oil, the specific base slurry formula is: 225 parts of 5# white oil + 3.75 parts of primary emulsifier HIEMUL + 10.00 parts of auxiliary emulsifier HICOAT + 3.25 parts of wetting agent MOWET + 0.75 parts of shearing agent ML-CSON + 7.50 parts of organic soil MOGEL + 25 parts of 30% calcium chloride solution + 7.5 parts of calcium oxide + 15 parts of fluid loss reducer TYODF-101 + 500 parts of barite powder.

[0032] Preparation of oil-based drilling fluid: 225 mL of 5# white oil was added to a 1000 mL stirring cup, followed by 3.75 g of primary emulsifier HIEMUL, 10.00 g of auxiliary emulsifier HICOAT, 3.25 g of wetting agent MOWET, and 0.75 g of shearing agent ML-CSON. The mixture was stirred at 12000 r / min for 10 min, and then 7.50 g of organic soil MOGEL was added. The mixture was stirred at 12000 r / min for 10 min. 25 mL of calcium chloride aqueous solution (calcium chloride mass percentage concentration 30%) was slowly added and stirred at high speed for 20 min. 7.5 g of calcium oxide and 15 g of filtrate reducer HIFLO were added and stirred at high speed for 20 min. 500 g of barite was added and stirred at high speed for 30 min to obtain the base slurry of the oil-based drilling fluid. The prepared drilling fluid density was 2.0 g / cm 3 .

[0033] Five identical base slurries were prepared according to the above method, wherein 1.0 g, 2.0 g, 3.0 g, and 4.0 g of titanium oxide-modified graphite carbon nitride nanocomposite plugging agent were added to four of the base slurries, respectively, to prepare four oil-based drilling fluids with different plugging agent contents ranging from 0.5% to 2.0%. In order to further illustrate the effects of the titanium oxide-modified graphite carbon nitride nanocomposite plugging agent and the oil-based drilling fluid of the present invention, the performance tests were carried out on the titanium oxide-modified graphite carbon nitride nanocomposite plugging agent and the oil-based drilling fluid prepared in Example 1 and Example 2.

[0034] 3. Performance Test

[0035] 1. Particle size test of titanium oxide modified graphite phase carbon nitride nanocomposite plugging material

[0036] The particle size of the titanium oxide modified graphite phase carbon nitride nanocomposite plugging agent was tested using the Bettersize 2600LD laser particle size analyzer produced by Dandong Better Instrument Co., Ltd. The particle size test results of the titanium oxide modified graphite phase carbon nitride nanocomposite plugging agent prepared in the two embodiments are as follows: Figure 1 , Figure 2 The particle size distribution of the titanium oxide modified graphite phase carbon nitride nanocomposite plugging agent of the present invention is between 350 and 620 nm, and the average particle size is 500 nm, indicating that the plugging agent synthesized by the present invention is nano-sized, and the plugging agent has a wide distribution range and can effectively plug nanopores of different nano-sized sizes.

[0037] 2. Test of drilling fluid rheological properties and water loss wall building performance

[0038] According to the standard GB / T16783.2-2012 "Field Test of Drilling Fluids in Petroleum and Natural Gas Industry Part 2: Oil-based Drilling Fluids", the rheological properties and water loss wall-forming properties of the drilling fluids prepared in the steps were tested before and after aging, and the results are recorded in Table 1.

[0039] Table 1 Drilling fluid rheological properties and filtration performance record

[0040]

[0041] Note: AV—apparent viscosity, in mPa·s; PV—plastic viscosity, in mPa·s; YP—dynamic shear force, in Pa; API—normal temperature medium pressure filtration loss, in mL; HTHP—high temperature and high pressure filtration loss, in mL, the temperature of HTHP is 120℃ and the pressure is 3.5MPa.

[0042] As shown in Table 1, the oil-based drilling fluid prepared with titanium oxide-modified graphite phase carbon nitride nanocomposite plugging agent as plugging agent in Example 1 and Example 2 has an apparent viscosity AV in the range of 39-44 mPa·s, a plastic viscosity PV in the range of 30.5-34 mPa·s, and a YP / PV value in the range of 0.25-0.29, indicating that the oil-based drilling fluid has a high carrying capacity for rock cuttings and has a small flushing effect on the well wall. After adding titanium oxide-modified graphite phase carbon nitride nanocomposite plugging agent, the AV and PV values ​​increase with the increase in the amount of addition, and the overall change rate is less than 20%, indicating that the plugging agent has good compatibility with the oil-based drilling fluid. In addition, the high-temperature and high-pressure filtration loss of the oil-based drilling fluid is significantly reduced with the increase in the amount of plugging agent, and the demulsification voltage is larger, so the drilling fluid prepared by a titanium oxide-modified graphite phase carbon nitride nanocomposite plugging agent synthesized by the present invention has better performance than the base slurry.

[0043] 3. Drilling fluid plugging performance test

[0044] An artificial core was used to simulate the formation with nano-micrometer pores and fractures. The average flow rate of the drilling fluid system in the artificial core was measured. The permeability K=Qμl / (AΔP) of the artificial core before and after the addition of the titanium oxide-modified graphite phase carbon nitride nanocomposite plugging agent was calculated by Darcy's formula, thereby calculating the plugging rate of the titanium oxide-modified graphite phase carbon nitride nanocomposite plugging agent on the artificial core and evaluating its plugging performance. The plugging effect record table of the titanium oxide-modified graphite phase carbon nitride nanocomposite plugging agent on the artificial core is shown in Table 2. The plugging rate is (initial permeability-permeability after plugging) / initial permeability×100%.

[0045] Table 2 Artificial core plugging test table

[0046] Core Drilling fluid type <![CDATA[Core permeability / 10 -3 mD]]> Blockage rate % 1 Base slurry 4.78 — 2 Base slurry + 0.5% Example 1 1.06 77.8 3 Base slurry + 0.5% Example 2 0.91 80.9 4 Base slurry + 1.0% Example 1 0.64 86.6 5 Base slurry + 1.0% Example 2 0.52 89.1 6 Base slurry + 1.5% Example 1 0.35 92.6 7 Base slurry + 1.5% Example 2 0.30 93.7 8 Base slurry + 2.0% Example 1 0.32 93.3 Base slurry + 2.0% Example 2 0.30 93.7

[0047] Note: The core length is 5 cm and the diameter is 2.5 cm.

[0048] As can be seen from Table 2, the titanium oxide-modified graphite phase carbon nitride nanocomposite plugging agent in Example 1 and Example 2 can effectively reduce the permeability of the artificial core, and the plugging effect is good. When the amount of the titanium oxide-modified graphite phase carbon nitride nanocomposite plugging agent is 0.5%, the permeability of the core decreases by 77.8% and 80.9%, respectively. As the amount of the titanium oxide-modified graphite phase carbon nitride nanocomposite plugging agent increases, the plugging effect is better. When the amount is increased by more than 1.5%, the permeability is still decreasing, but the decrease is almost not obvious, indicating that the optimal addition amount of the titanium oxide-modified graphite phase carbon nitride nanocomposite plugging agent of the present invention is 1.5%. According to Table 1, the 1.5% plugging agent addition has good compatibility with the oil-based drilling fluid, and can improve the rheological properties and water loss wall-building properties of the drilling fluid.

[0049] The above description is only a preferred embodiment of the present invention and does not constitute any form of limitation to the present invention. Although the present invention has been disclosed as a preferred embodiment as above, it is not intended to limit the present invention. Any technician familiar with the profession can make some changes or modifications to equivalent embodiments of equivalent changes using the technical contents disclosed above without departing from the scope of the technical solution of the present invention. However, any simple modification, equivalent change and modification made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention still falls within the scope of the technical solution of the present invention.

Claims

1. A titanium oxide modified graphite phase carbon nitride nanocomposite plugging agent, characterized in that: The raw materials for synthesizing the titanium oxide modified graphite phase carbon nitride nanosheet composite plugging agent include melamine, tetrabutyl titanate, phosphorous acid, glycerol, ethanol, ethylene glycol, an initiator, and deionized water; the preparation steps are as follows: Step 1, adding tetrabutyl titanate to a dispersion of deionized water, ultrasonically dispersing, then dropping an initiator while stirring, reacting at 50-60° C., cooling to room temperature, centrifugally filtering, ultrasonically dispersing, filtering, adjusting the sol concentration, and obtaining a pure titanium oxide sol; Step 2: Preparation of graphite phase carbon nitride nanosheets: Melamine and phosphorous acid are added to deionized water to dissolve, and then stirred for a period of time under water bath conditions, and then placed in a sealed high-pressure reactor for reaction after stirring, and after the reaction, filtered, washed, and dried to obtain a precursor; glycerol and ethanol are mixed to obtain a mixed solution; the precursor is added to the mixed solution, and then refluxed under oil bath conditions, cooled, washed with anhydrous ethanol, and dried to obtain an intermediate product; calcining the intermediate product to obtain graphite phase carbon nitride nanosheets; Step 3: Preparation of titanium oxide modified graphite phase carbon nitride nanocomposite plugging agent: First, ethanol and ethylene glycol are mixed to obtain a mixed solution; the titanium oxide sol prepared in step 1 is added, stirred and ultrasonically dispersed to obtain a titanium oxide sol dispersion; the graphite phase carbon nitride nanosheets prepared in step 2 are added, stirred and ultrasonically dispersed to obtain a graphite phase carbon nitride nanosheet dispersion; the two dispersions are then mixed, ultrasonically dispersed, reacted at 50-60° C., cooled to room temperature, filtered, washed, dried, and calcined at high temperature to obtain a titanium oxide-modified graphite phase carbon nitride nanocomposite plugging material; The volume ratio of tetrabutyl titanate to deionized water in step 1 is 10 mL:40 mL, and the initiator is one of hydrogen chloride (HCl), sulfuric acid (H2SO4), sodium hydroxide (NaOH), and potassium hydroxide (KOH); In step 2, the dosage ratio of melamine, phosphorous acid and deionized water is 1:1-5 g:100 mL, the volume ratio of glycerol and ethanol mixed solution is 10 mL:10-60 mL; the dosage ratio of the precursor to the mixed solution is 0.6 g:10-50 mL; In the step 3, the volume ratio of the ethanol and ethylene glycol solutions is 1:1; the volume ratio of the titanium oxide sol to the ethanol and ethylene glycol mixed solution is 10-40 mL:40 mL; and the amount ratio of the graphite phase carbon nitride nanosheets to the ethanol and ethylene glycol mixed solution is 10-40 mg:40 mL.

2. The titanium oxide modified graphite phase carbon nitride nanocomposite plugging agent according to claim 1, characterized in that: In step 1, the concentration of titanium oxide sol is adjusted to 20 mg / mL; in step 2, the temperature of the water bath is 60-90° C., and the stirring period is 0.5-2 h; the temperature of the reaction in the high-pressure reactor is 120-200° C., and the time is 6-24 h.

3. The titanium oxide modified graphite phase carbon nitride nanocomposite plugging agent according to claim 1, characterized in that: In step 2, the temperature of the oil bath is 60-120° C., and the reflux time is 2-6 hours; the temperature of the calcination is 350-600° C., and the time is 1-5 hours.

4. The titanium oxide modified graphite phase carbon nitride nanocomposite plugging agent according to claim 1, characterized in that: The drying temperature in steps 2 and 3 is 60-150° C., and the drying time is 5-10 hours; the high-temperature calcination in step 3 is 500-600° C., and the calcination time is 2-4 hours.

5. An oil-based drilling fluid, characterized in that: The drilling fluid is added with the titanium oxide modified graphite phase carbon nitride nanocomposite plugging agent as claimed in claim 1, and contains white oil, organic soil, primary emulsifier, auxiliary emulsifier, wetting agent, calcium oxide, calcium chloride solution (mass fraction is 25-30%), filtrate reducer, weighting agent, shearing agent and plugging agent.

6. The oil-based drilling fluid according to claim 6, characterized in that: The base oil is 5# white oil, the organic soil is MOGEL, the primary emulsifier is HIEMUL, the auxiliary emulsifier is HICOAT, the wetting agent is MOWET, the filtrate reducer is HIFLO, the weighting agent is barite powder, the shearing agent is ML-CSON, and the plugging agent is the titanium oxide-modified graphite phase carbon nitride nanocomposite plugging agent synthesized in this article.

7. The oil-based drilling fluid component according to claim 7, characterized in that: The composition of the drilling fluid is as follows, in parts by weight: 225-227 parts of 5# white oil, 7-8 parts of organic soil MOGEL, 3.6-3.8 parts of primary emulsifier HIEMUL, 9.8-10.2 parts of auxiliary emulsifier HICOAT, 3.2-3.3 parts of wetting agent MOWET, 14.5-15.5 parts of filtrate reducer HIFLO, 0.7-0.8 parts of shear enhancer ML-CSON, 24-26 parts of 25-35% calcium chloride solution, 7.3-7.7 parts of calcium oxide, 1.25-3.75 parts of titanium oxide modified graphite phase carbon nitride nanocomposite plugging agent, 250-600 parts of barite powder, and a density of 1.5-2.1 g / cm 3 .